2019
DOI: 10.1200/jco.2019.37.15_suppl.tps8056
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib, lenalidomide, and dexamethasone (VRd) ± daratumumab (DARA) in patients (pts) with newly diagnosed multiple myeloma (NDMM) for whom transplant is not planned as initial therapy: A multicenter, randomized, phase III study (CEPHEUS).

Abstract: TPS8056 Background: DARA is a human, anti-CD38 IgGκ monoclonal antibody that significantly reduced the risk of progression/death with a manageable safety profile across several phase 3 studies in relapsed/refractory MM and NDMM. DARA + VRd (D-VRd) demonstrated efficacy and tolerability in the safety run-in cohort of the ongoing phase 2 GRIFFIN study that included transplant-eligible NDMM pts. To determine whether D-VRd demonstrates efficacy and tolerability in NDMM pts for whom transplant is not intended as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…More recent studies are now including the monoclonal antibodies daratumumab, elotuzumab, and isatuximab in the upfront setting as part of a quadruplet regimen that includes a monoclonal antibody with standard triplet combinations to improve depth of response and thus outcomes 52138139140141142143144…”
Section: Future Directionsmentioning
confidence: 99%
“…More recent studies are now including the monoclonal antibodies daratumumab, elotuzumab, and isatuximab in the upfront setting as part of a quadruplet regimen that includes a monoclonal antibody with standard triplet combinations to improve depth of response and thus outcomes 52138139140141142143144…”
Section: Future Directionsmentioning
confidence: 99%
“…However, there was no significant difference in the stem cell harvest between the D or the control arm in either of these two clinical trials, albeit the goal of the stem cell harvest was relatively low at approximately 5 × 10 6 CD34 cells/kg [ 10 ] and the liberal application of plerixafor was encouraged. Results of the ongoing phase III studies PERSEUS investigating the quadruple regimen of D-VRD in NDMM are much awaited [ 20 , 21 ]. Minimal residual disease (MRD) status is emerging as a robust predictor of clinical outcome independent of cytogenetic risk factors, treatment regimen, or disease burden and there have been attempts for MRD risk-adapted treatment approaches to offer treatment-free intervals or intensification of treatment in some situations [ 22 , 23 ].…”
Section: Monoclonal Antibodies Are Increasing Becoming An Important Part Of Upfront Therapymentioning
confidence: 99%
“…The primary endpoint is the rate of minimal residual disease by next-generation sequencing. 37 The CEPHEUS trial is anticipated to provide valuable information about the safety and efficacy of D-VRd in older adults who are newly diagnosed with multiple myeloma.…”
Section: Cepheus: Ongoing Trial Using Daratumumab In Older Adultsmentioning
confidence: 99%
“…Although lenalidomide, either alone or in combination, is a part of the current treatment standard for older adults, the treatment landscape for myeloma is rapidly evolving. It is likely that the role of lenalidomide will continue to evolve as new drugs and combinations demonstrate efficacy in older adults with myeloma, whether it be through novel drug combinations as in the CEPHEUS trial, 37 or through lenalidomide-free regimens. The ALCYONE trial showed the efficacy of a lenalidomide-free regimen by using the combination of daratumumab plus bortezomib, melphalan, 56 While the results support a viable lenalidomide-free treatment regimen, a direct comparison of this regimen versus lenalidomide-containing regimens has not been conducted.…”
Section: Evolving Treatment Options For Older Adultsmentioning
confidence: 99%